Influences of conditional, environmental and social values, risk and cost on consumers’ willingness to pay for water tariff - Abdul Wahid, Nabsiah; Kamalul Ariffin, Shaizatulaqma; Haron, Amran (Innovare Academics Sciences PVT. LTD, 2020)
Water is treated as a public or social good in Malaysia. Malaysians believe that providing good quality water for households’ use is the government’s responsibility. The government has been subsidizing the cost of water for its population since pre-Independence Day. However, the increased cost of providing good quality water to the public meant that the current water tariff charged needs to be re-evaluated. This study investigates the role played by various factors, namely, perceived conditional value, perceived environmental value, social norm, perceived risk and perceived cost on Malaysian consumers’ willingness to pay for water provided to households. The target of the study was paid water consumers in Malaysia. The results of online survey participated by 867 willing paid water consumers analysed by Partial Least Square-Structural Equation Modelling (PLS-SEM) show that only perceived conditional value, perceived environmental values, and perceived risk were significantly related to Malaysian consumers’ willingness to pay (WTP) for proposed higher water tariff while social norm and perceived cost show insignificant influences on consumers’ WTP. Overall, conditional value shows the strongest effect towards consumers’ WTP. The study’s findings have provided insights for the government and water providers on how Malaysian household water consumers behave on the issue of implementing higher water tariff. It is now known that Malaysian consumers’ perceived values, in particular, conditional value as well as risks they perceived to be existent are significant in influencing their WTP behaviour on proposed higher water tariff. These findings suggest that any future plan to increase current water tariff may not be accepted by the public unless their perceived values and risk on the issue are considered and inserted in any of the water education campaigns by the government and water providers.